Analisis Fiqih Siyasah Terhadap Strategi Pencegahan Paham Radikalisme di Kabupaten Padang Lawas Utara (Studi Kementerian Agama PALUTA) - Hakim Harahap, Akmal; Khalid, Khalid (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
The purpose of this paper is to find out what is the strategy for preventing radicalism according to the perspective of fiqh siyasah? and what is the strategy for preventing radicalism according to the Ministry of Religion of North Padang Lawas? The writing methodology used by the researcher is the researcher using a qualitative descriptive research method or what is often called field research. Then the data is described, analyzed, and discussed to answer the problem. The source of data collected is primary data taken from a number of respondents. To obtain valid data, this study uses several data collection methods, namely interviews and observations. While secondary data can be done through the library aims to collect data and information with the help of books in the library. The results of this study have revealed: First, in this case the strategy taken by the Ministry of Religion of North Padang Lawas is to anticipate preventive actions against residents of North Padang Lawas through the Ministry of Religion in North Padang Lawas Regency in order to develop tolerant Islam and also cooperate with other parties, and carry out refresciptive actions by holding a grand tabligh, providing direction, socialization. Second, according to the fiqh perspective, siyasah has not been implemented in accordance with Islamic law.